Hannah Arendt - Hill, Samantha Rose (Critical lives, 2021)
Hannah Arendt is one of the most renowned political thinkers of the twentieth century, and her work has never been more relevant than it is today. Born in Germany in 1906, Arendt published her first book at the age of twenty-three, before turning away from the world of academic philosophy to reckon with the rise of the Third Reich. After World War II, Arendt became one of the most prominent - and controversial - public intellectuals of her time, publishing influential works such as The Origins of Totalitarianism, The Human Condition, and Eichmann in Jerusalem. Samantha Rose Hill weaves together new biographical detail, archival documents, poems, and correspondence to reveal a woman whose passion for the life of the mind was nourished by her love of the world. --